Challenges and Future Directions in Quantifying Terrestrial Evapotranspiration - Koong Yi; Gabriel B. Senay; Joshua B. Fisher; Lixin Wang; Kosana Suvočarev; Housen Chu; Georgianne W. Moore; Kimberly A. Novick; Mallory L. Barnes; Trevor F. Keenan; Kanishka Mallick; Xiangzhong Luo; et al. (Water Resources Research)
Abstract Terrestrial evapotranspiration is the second‐largest component of the land water cycle, linking the water, energy, and carbon cycles and influencing the productivity and health of ecosystems. The dynamics of ET across a spectrum of spatiotemporal scales and their controls remain an active focus of research across different science disciplines. Here, we provide an overview of the current state of ET science across in situ measurements, partitioning of ET, and remote sensing, and discuss how different approaches complement one another based on their advantages and shortcomings. We aim to facilitate collaboration among a cross‐disciplinary group of ET scientists to overcome the challenges identified in this paper and ultimately advance our integrated understanding of ET.